Fatty acid profile in dorsal fat and Longissimus dorsi muscle of post-weaned hairless piglets fed with arboreal leaves meal - Castellón-Moya, Claudia Teresita; Lemus-Flores, Clemente; Dzib-Cauich, Dany Alejandro; Oney-Montalvo, Julio Enrique; Grageola-Núñez, Fernando; Bugarín-Prado, Job Oswaldo; Pat-Moreno, Nitmar Itzel (Revista Científica de la Facultad de Ciencias Veterinarias, 2025)
In the present investigation, the inclusion  of  flours  from the arboreal Cnidoscolus aconitifolius (Chaya), Morus alba (Mulberry) and Moringa oleifera (Moringa) in the conventional Corn-Soy diet was compared to evaluate the lipid profile in the Longisimus dorsi (LD) and in the back fat (DF) of the post- weaned Pelon pigs. A sample of 28 animals, 24 days old, post- weaned, was used. These were divided into four experimental groups, homogenized by sex and weight and subjected to a seven-day adaptation period. They were  subsequently  fed ad libitum for 28 days and slaughtered after 59 days. For the statistical analysis of the variables associated with the fatty acid profile (saturated, monounsaturated and polyunsaturated), a randomized block design statistical model was used, with the aim of determining whether there were statistically significant differences (P˂0,05) between  the variables associated with the fatty acid profile and the diets. It was shown that the SFA variable in LD and GD was higher in piglets fed with Mulberry, the MUFAs in LD and GD were higher in the animals of the Control group and the values of the PUFAs in LD and GD increased in the piglets supplemented with Moringa and Chaya, allowing to conclude that Mulberry increases the values of SFA in LD and GD of Hairless pigs; on the other hand, Chaya and Moringa increase the content of the PUFAs in LD and GD of these animals.